(3GdJdNjU aj JaSjQ GdbQBf GdYRjRs - (3GdchGTj, GdehUdj, CHh GdYHGS, ehab GdOjf, CMeO Hf jhSa Hf GdMSf Hf QGaY, J (B680(3g`s ((3YHO GdQMef Hf eMeO Ydjs)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg(B...(3hHYO adeG QCjJ GdcJGH GdYRjR aj ZGjI GdEYLGR hfgGjI GdEjLGR, hCf dG SHjd Edi eYQaI Pdc EdG HJhajb Edgj Ch HJhbja fHhj(B...s
(3BNQgG (B:s
(3jfJgj HJaSjQ ShQI Gdcga, hBNQg(B: (3agh eYUhe KeGfjI CjGe ef cd aJfI aEf NQL GdOLGd aj GdEjGe GdKeGfjI YUeg ef aJfI GdOLGd(B...(3bO Je GdfUa GdChd ef gPG GdcJGHs
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdbQBfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B274s
(3cTa GdXfhf(B:(3L(B1(3,U(B457s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs